HUMAN RIGHTS VIOLATIONS AND CRIMINAL ACCOUNTABILITY IN ARMED CONFLICT AND THE PLACE OF INTERNATIONAL HUMANITARIAN LAW - AGBO SOPHIA ABUH (International Studies Journal)
This study investigates the effectiveness of international humanitarian law (IHL) in ensuring accountability for human rights violations within contemporary armed conflicts. While previous research has addressed the application of IHL in specific conflict contexts, this study adopts a broader, comparative approach to evaluate the adequacy of existing legal frameworks in both international and non-international armed conflicts. The research examines how evolving conflict dynamics, including asymmetric warfare, terrorism, and insurgencies, present unique challenges to the enforcement of IHL. Employing a qualitative methodology, it analyzes legal documents, case law, and historical precedents while integrating perspectives on state and non-state actors' accountability. Unlike previous studies that often focus on a single conflict or geographic region, this research assesses global case studies to identify recurring enforcement gaps in IHL, particularly regarding the roles of international bodies like the United Nations and the International Criminal Court (ICC). Findings reveal that while IHL principles, such as distinction and proportionality, provide a solid framework for civilian protection, enforcement mechanisms remain inconsistent, especially in conflicts involving non-state actors. This study contributes to the literature by offering a comprehensive, cross-regional analysis of IHL's applicability in modern warfare and proposing targeted reforms to enhance accountability for human rights violations across diverse conflict scenarios. These insights aim to inform policy developments and strengthen international legal mechanisms for improved protection of civilians and justice for war victims.